2016
DOI: 10.1016/j.jagp.2016.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults' Perspectives on Clinical Research: A Focus Group and Survey Study

Abstract: Objectives Clinical trials can benefit from the patient perspectives to inform their design, such as choice of outcome measures. We engaged older adults in focus groups and surveys to get their perspective regarding needs in clinical research. The goal was to inform the development of a new clinical trial of medication strategies for treatment-resistant depression in older adults. Methods Older adults with depression participated in focus groups and a subsequent survey in St. Louis and New York. They were qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Implications for research PST showed positive short-term effects for reducing depressive symptoms, although it did not show effects upon other outcomes. Large scale RCTs, therefore, need to be powered to assess the effects of PST upon a more comprehensive set of outcomes more relevant to older people, particularly functioning (a key frailty outcome) (Ferrucci et al, 2004) and quality of life (Lenze et al, 2016), especially in the long term. Evaluation of hospitalizations, social care use, and cost-effectiveness is also vital to assist commissioning decisions, as home-based services are potentially costly but may deliver long-term costsavings in health or social care use.…”
Section: Implications For Practicementioning
confidence: 99%
“…Implications for research PST showed positive short-term effects for reducing depressive symptoms, although it did not show effects upon other outcomes. Large scale RCTs, therefore, need to be powered to assess the effects of PST upon a more comprehensive set of outcomes more relevant to older people, particularly functioning (a key frailty outcome) (Ferrucci et al, 2004) and quality of life (Lenze et al, 2016), especially in the long term. Evaluation of hospitalizations, social care use, and cost-effectiveness is also vital to assist commissioning decisions, as home-based services are potentially costly but may deliver long-term costsavings in health or social care use.…”
Section: Implications For Practicementioning
confidence: 99%
“…Psychological well‐being has been identified, along with symptomatic remission and side effects on sleep, as being one of the most important outcomes by patients suffering from depression 9,45 . Our participants experienced an 8.9 T‐score increase in overall psychological well‐being with 4 weeks of treatment with IV ketamine.…”
Section: Discussionmentioning
confidence: 85%
“…Psychological well-being has been identified, along with symptomatic remission and side effects on sleep, as being one of the most important outcomes by patients suffering from depression. 9,45 Our participants experienced an 8.9 T-score increase in overall psychological well-being with 4 weeks of treatment with IV ketamine. In a recent large comparative study of antidepressant pharmacotherapy in late-life TRD conducted by the same investigators using the same measure of psychological well-being, participants experienced increases of 4.1, 3.7, and 2.6 over 10 weeks of treatment with aripiprazole, bupropion, and lithium, respectively.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Participants are followed longitudinally, tracking traditional depressive symptom outcomes as well as critical geriatric outcomes, such as falls, based on perspectives from older adults with depression. 64…”
Section: Optimum: An Example Of a High-risk Cohortmentioning
confidence: 99%